Răspuns:
b=[tex](\sqrt{3} -3)^2[/tex] - [tex]\sqrt{(\sqrt{3} - 2)^2}[/tex] + [tex]\sqrt{75}[/tex] = 2 (7-[tex]\sqrt{3}[/tex])
Explicație pas cu pas:
[tex](\sqrt{3} -3)^2 = 3 - 6\sqrt{3} + 9[/tex]
[tex]\sqrt{(\sqrt{3} - 2)^2}[/tex]= [tex]\sqrt{3}-2[/tex]
[tex]\sqrt{75}[/tex] = 5[tex]\sqrt{3}[/tex]
b = [tex]3 - 6\sqrt{3} + 9[/tex] - ([tex]\sqrt{3}-2[/tex]) + 5[tex]\sqrt{3}[/tex] = [tex]3 - 6\sqrt{3} + 9[/tex] - [tex]\sqrt{3}+2[/tex] + 5[tex]\sqrt{3}[/tex] = 14 - [tex]2\sqrt{3}[/tex] = 2 (7-[tex]\sqrt{3}[/tex])